Concurrent Spacecraft Attitude and Orbit Estimation with Attitude Control Based on Magnetometer, Gyro, and GPS Measurements through Extended Kalman Filter - Tamer Mekky Ahmed Habib (Journal of Basic & Applied Sciences, 2014)
The main objective of this research is to provide attitude estimation, orbit estimation, and attitude control algorithms suitable for application to the next Egyptian scientific satellite. Concurrent spacecraft orbit and attitude estimates must be suitable for usage by the attitude control algorithm. The developed estimation algorithms are able to deal with sever tumbling conditions characterized by large initial attitude, angular velocity and position estimation errors. The estimation algorithms could provide attitude estimates within 0.5o(3-σ) and 60 m (3-σ) for the position estimation errors. The attitude control algorithm developed is able to bring the spacecraft from its initial tumbling conditions to nadir pointing within an error of only 0.5o (3-σ).